The effectiveness of using telemedicine on blood sugar control and maternal complications and neonatal outcomes of women with gestational diabetes during covid-19: a quasi-experimental study - Sanaz Yasrebinia; Mina Zeynalzade; Mansour Rezaei (Mashhad University of Medical Sciences, 2023)
Introduction: Women with high-risk pregnancies, including women with gestational diabetes, are much more prone to COVID-19 than other pregnant women, so the use of telemedicine programs is very necessary for these women in self-care of their disease during the Covid-19 pandemic; Therefore, the present study was performed with aim to determine the effectiveness of using telemedicine on blood sugar control and maternal complications and neonatal outcomes of women with gestational diabetes during covid-19. Methods: This quasi-experimental study was conducted with the participation of 88 women with gestational diabetes in Taleghani Hospital, Tabriz in 2020-2021. The participants were randomly assigned to two groups of intervention (use of telemedicine technology) and control (conventional method). Weight control, blood sugar, maternal complications and neonatal outcomes were compared between the two groups. Data analysis was done using SPSS statistical software (version 25) and t-test and chi-square test. P<0.05 was considered statistically significant. Results: The mean fasting blood sugar during the study (P=0.045) and HA1C level before delivery (P=0.034) were significantly lower in the intervention group than the control group. In the control group, the number of instrumental deliveries (P=0.045) and cesarean section (P=0.041) was significantly higher than the intervention group. Also, infant hypoglycemia (P=0.033) and high infant weight (P=0.044) were significantly higher in the control group than the intervention group. Conclusion: Telemedicine was able to control blood sugar, reduce HA1C before delivery, reduce the number of non-physiological births, reduce hypoglycemia and reduce high birth weight in women with gestational diabetes during the covid-19 pandemic.